COMMERCIAL TRAWL FISHERIES OFF KAKINADA DURING 1967-70 - Muthu, M S; Narasimham, K A; Rao, G Sudhakara; Sastry, Y Appanna; Ramalingam, P (Indian Journal of Fisheries, 2011)
OS Kakinada, both exploratory and experimental trawling by the Central and State government organisations were in progress since 1960. But the commercial exploitation of the resources by the industry with small-sized trawlers began only in 1964. Since then, there is a continuous growth over the years both in the number and size oi the trawlers. In view of the importance of detailed knowledge about tiie various aspects of a growing fishery, the relevant particulars collected during 1967-70 are presented in this article